Parent’s food literacy and adolescents nutrition literacy influence household’s food security and adolescent’s malnutrition and anemia: Findings from a national representative cross sectional study - Hoteit, Maha; Mohsen, Hala; Hanna-Wakim, Lara; Sacre, Yonna (Frontiers in Nutrition, 2022)
Food and nutrition literacy are widely fundamental to improve the food security and reduce the double burden of malnutrition and iron deficiency in low-and middle-income countries. This study aimed 1) to assess the nutrition literacy (NL) of Lebanese adolescents and their parents’ food literacy (FL),. 2) to investigate the impacts of adolescents’ NL and parental FL on a) the household food security, b) the and adolescents’ self-reported food security c) and the adolescents’ nutrition status with focus on malnutrition and anemia. Around 45.0% of the adolescents were nutritionally illiterate, and nearly half (47.8%) of parents had poor FL. Around 68.2% and 54.0% of the households and adolescents were food insecure, respectively. Moreover, 6.7%, 4.7%, 32.2%, and 16.7% of the adolescents were stunted, thin, overweight/obese, and anemic, respectively. Poor parental FL increased the risk of household FI by 2.7 times, p<0.001. Adolescents’ nutrition illiteracy increased their FI risk by 60.0% (p=0.02). The number of offspring, household income, crowding status, and participants’ residence also influenced the percentage of FI and malnutrition prevalence among households and adolescents. Improvements in FL and NL are promising to mitigate FI malnutrition in Lebanon.